Analisis Pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDES) pada Masa Pandemi Covid-19 (Studi Kasus di Desa Kemiri Kecamatan Puspo Kabupaten Pasuruan) - Kusumas Tutik Wahyuningsah; Moh. Amin; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The Village Expenditure Budget and Revenue (APBDES) is a village financial plan based on village regulations that contains estimates of sources of income and expenditure to support the needs of village development programs related to a period. This study aims to determine the management of the Village Revenue and Expenditure Budget (APBDes) during the Covid-19 pandemic in Kemiri Village, Puspo District, Pasuruan Regency. This study used qualitative research methods. Data collection techniques using, observation, interviews and documentation. Data analysis techniques using data reduction, data presentation then conclusions. Based on the research results, it is known that the total income of Kemiri Village in 2021 is Rp. 1.615.608.903,39 and the amount of spending spent to finance operational activities and spending for Kemiri Village was Rp. 1.628.209.228,20. From the difference between the amount of income and the amount of spending, it can be seen that costs are greater than the income earned by Kemiri Village. So that in the financial management of Kemiri Village in 2021 it is said to experience a deficit.Keywords: APBDes, village financial management, village expenditure